Vertical Distribution of Phosphorous Fractions and Bioavailability of the Nutrient in the Southern Indian Ocean - Muhammed Nayeem Mullungal (21385463) (2022)
The study evaluated concentration, vertical distribution, and bioavailability of phosphorus fractions in the Indian Ocean core sediments. Sediment samples were collected from two sites in the Indian Ocean during January–February 2010 using gravity corer. Phosphorus fractions in sediments were analyzed by a modified sequential extraction procedure (SEDEX). The vertical profile revealed silt and clay as dominant grain size fractions in both cores. The enriched levels of organic carbon were observed in samples due to adsorption on fine grained sediments. Loosely bound P was the most dominant fraction, and its higher concentration in sediments was due to increased productivity and subsequent inputs of biogenic components. Detritus from marine organisms and lower oxygen concentrations (depleted Eh values) enhanced the production of authigenic P. The lower iron bound P fraction at specific depths was attributed to the nature of Fe minerals present within sediments. Decreased level of organic phosphate fraction was due to mineralization. The presence of Detrital P, the diagenetically stable form of P, might be due to inputs from the Himalayan, peninsular Indian, and Sri Lankan regions. The biogenic form was the dominant phosphate fraction throughout the cores suggesting the dissolution of fish debris. Estimated bioavailable phosphorous (BAP) ranged from 82.2 to 98.7% in Core I and from 90.21 to 92.98% in Core II, suggesting the fact that a major portion of the phosphate was bioavailable and hence the alterations in environmental conditions can release the BAP to water column resulting in nutrient enrichment. Other Information Published in: International Journal of Environmental Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41742-022-00448-z